Biocultural Evolution and the Imagination: Outlining Scientific Perspectives for Theological Reflection - Lorrimar, Victoria (Heythrop journal, 2025)
The human imagination is studied widely across both the sciences and the humanities, yet there is a lack of conceptual clarity for interdisciplinary engagement. This article surveys a sample of recent scientific research on the imagination, focusing on creativity and storytelling, to demonstrate how an understanding of the biocultural evolutionary context may yield helpful insights for contemporary theological anthropology. Niko Tinbergen's levels of analysis (mechanism, function, phylogeny, and ontogeny) are used as a guiding framework to structure the scientific content. The final section sketches some of the recent trajectories in theological anthropology that are supported by a biocultural evolutionary perspective on the imagination, namely those that emphasise the hybridity of human being and resist human/non-human binaries. This exercise in examining scientific perspectives for theological construction is reflected upon in the context of a broader science-engaged theology methodology.